Combined Effects of Virtual Reality and Computer Game-Based Cognitive Therapy on the Development of Visual-Motor Integration in Children with Intellectual Disabilities: A Pilot Study - Si-nae Ahn (Occupational Therapy International)
Purpose. Visual-motor integration is a good indicator of a child’s overall developmental and functional level. This study investigated the combined effects of virtual reality (VR) and computer game-based cognitive therapy on the development of visual-motor integration in children with intellectual disabilities. Methods. The study used a single-group pre-post study design and 13 children with intellectual disabilities who were recruited from a community rehabilitation center participated in the study. We used the Wii VR video game and the CoTras computer game to deliver cognitive therapy over 12 sessions. The Bruininks-Oseretsky Test of Motor Proficiency-2 (BOT-2) was used to evaluate motor function related to visual-motor integration to identify changes in function, and the Developmental Test of Visual Perception-2 (DTVP-2) was used to assess changes in visual perception function associated with visual-motor integration. Results. The VR and computer game-based cognitive therapy has shown significant difference in total standard score of BOT-2 associated with visual-motor integration representing improved motor function (p<0.01). Comparison of the DTVP-2 scores showed the significant difference in visual-motor integration of spatial relation and visual-motor speed (p<0.05), motor-reduced visual perception (p<0.01), and general visual perception (p<0.01). Conclusions. Results of this study provide useful evidence supporting the possibility of combined VR and computer game-based cognitive therapy for children with intellectual disabilities.